Carotid Intima-Media Thickness in Patients with Subclinical Hypothyroidism: A Prospective Controlled Study - Soto-García, Anally J.; Elizondo-Riojas, Guillermo; Rodriguez-Gutiérrez, Rene; Mancillas-Adame, Leonardo G.; González-González, J. Gerardo (Clinical and investigative medicine, 2021)
The association between subclinical hypothyroidism (SCH) and cardiovascular risk, particularly with a TSH <10 µIU/ml, remains controversial. The objective of our study was to assess the association between SCH and cardiovascular risk through carotid intima-media thickness, and alternatively, to evaluate its change after treatment with levothyroxine. A total of 54 individuals were included in the study: 18 with SCH; 18 with overt hypothyroidism (OH); and 18 healthy controls (HC). The carotid intima-media thickness was measured in each group. In SCH, follow-up was performed at three and six months after the start of levothyroxine treatment. The mean age of the total population at baseline was 35.8 years. The median TSH in SCH was 6.15 µIU/ml. The carotid intima-media thickness (mean and standard deviation) was greater in SCH in comparison to the HC group: right common carotid artery (RCCA), 0.486 ± 0.106 mm and 0.413 ± 0.075 mm in SCH and HC, respectively, p=0.01 and left common carotid artery (LCCA), 0.511 ± 0.144 mm and 0.427 mm ± 0.090 in SCH and HC, respectively, p=0.03). In patients with SCH, there was a decrease in the carotid intima-media thickness after treatment with levothyroxine (RCCA and LCCA, p <0.05 at three and six months). There was an association between increased carotid intima-media thickness in patients with SCH in comparison with HC, even with a TSH <10 µIU/ml. The increase was reversed with levothyroxine therapy. The association of this increased thickness with important cardiovascular outcomes remains uncertain and should be evaluated in future studies.